Supply Chain Identification of Indonesian Specialty Coffee: A Case Study of Kayumas Coffee Using The FSCN Framework - Rahmadyahningrum, Aisya Risanda; Setiawati, Nia Rahmi (CITACONOMIA, 2025)
Downstream policy formulation in Indonesia’s specialty coffee sector remains constrained by fragmented data systems that fail to integrate production, processing, and market dimensions, particularly for smallholder-based supply chains. This study aims to identify and analyze the supply chain configuration of Kayumas specialty coffee from Situbondo, East Java, using Vorst’s Food Supply Chain Networks (FSCN) framework. A qualitative case study design was applied, with data collected through in-depth interviews using snowball sampling involving farmers, farmer group leaders, roastery owners, distributors, café owners, and consumers. Secondary data were obtained from documents and literature to support triangulation. Data were analyzed thematically across four FSCN dimensions: supply chain structure, management, resources, and business processes. The findings indicate that the Kayumas coffee supply chain is characterized by a smallholder-driven, trust-based governance structure operating through a hybrid push–pull system. While farmer groups play a central coordinating role in post-harvest processing and market access, the chain remains constrained by limited capital, weak digital infrastructure, informal contracting, and fragmented information flows. These constraints limit scalability, traceability, and performance measurement, thereby weakening adaptive downstream policy design. This study concludes that strengthening data integration, formal coordination mechanisms, and digital traceability systems is essential to enhance value creation, investment consistency, and smallholder participation in Indonesia’s specialty coffee economy. The findings provide empirical evidence to support more coherent, data-driven downstream policy formulation and supply chain development strategies